Policy evaluation on the distribution of disaster stimulant funds in Palu city - Nuraisyah Nuraisyah; Erdiyansyah Erdiyansyah; Aldi Aldi (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
This study aims to evaluate the distribution of disaster stimulant funds in Palu City. This study used a quantitative approach with descriptive statistics analysis. It is expected that the results of the study can be operationalized or applied at various levels of government, especially in disaster management. The population of this study was all stakeholders in disaster management in Palu City including the Regional Disaster Mitigation Agency, the Social Service, the Public Works Office, the Sub-District Office, the Village Office, and the Acceleration of Regional Development Executive Monitoring Team (TP4D). This study involved a total of 228 respondents. The determination of the sample used a census technique meaning that the entire population was used as samples. The results of this study showed that the distribution of disaster stimulant funds in Palu City was not effective as the fund was only enjoyed by certain groups and had not solved community problems. This means that there are many complaints from the affected community as they have not been registered as a beneficiary of stimulant funds.This research contributes to the development of public policies related to the policy of distributing stimulant funds for victims of natural disasters consisting of earthquakes, tsunamis, and liquefaction, so policy formulation needs to be designed comprehensively so that it becomes a recommendation for the future because policies related to earthquake, tsunami, and liquefaction disasters have not previously occurred anywhere in the world so that the findings of this study become recommendations for the government in handling increasingly complex natural disasters.